Observation of an anomalous SmA-SmC-SmA phase sequence in a bent-core liquid crystal derived from 4-cyanoresorcinol - Yu. P. Panarin; S. P. Sreenilayam; V. Swaminathan; C. Tschierske; J. K. Vij (Physical Review Research, 2020)
The physical properties and the phase transitions of a smectic liquid crystal material built from achiral bent-core molecules are investigated by electro-optics, polarizing microscopy, birefringence, and spontaneous polarization. This material is shown to exhibit a number of orthogonal and tilted smectic phases. The observation of an anomalous phase transition on cooling from a tilted to orthogonal antiferroelectric smectic phase at lower temperatures is made, and a proof of the evidence is presented. The importance of the biaxial anchoring term in the free energy is modeled and discussed.